THE EFFECT OF CALCINATION TEMPERATURE TO THE COMPOSITE CHARACTERISTICS OF TiO2SiO2 NANOPARTICLE - Della Dwi Ananda; Dina Kartika Maharani (Jurnal Sains Materi Indonesia, 2020)
THE EFFECT OF CALCINATION TEMPERATURE TO THE COMPOSITECHARACTERISTICS OF TiO2SiO2 NANOPARTICLE. Self-cleaning material is a material that utilizes the photocatalytic property to degrade organic and inorganic compounds with the help of UV light. One of the materials that have good photocatalytic property is TiO2, the photocatalytic property causes TiO2 to be amphiphilic: becomes hydrophilic when there is light and becomes hydrophobic when there is no light. The photocatalytic property of TiO2 can be improved with the addition of buffer material such as SiO2. TiO2SiO2 nanoparticle was synthesized using a sol-gel method with Titanium (IV) Isopropoxide (TTIP) precursors for TiO2 and Tetraethyl Orthosilicate (TEOS) precursors for SiO2 and followed by a variation of calcination temperature of 400 °C, 450 °C, 500 °C, and 550 °C for 2 hours. TiO2SiO2 composite was synthesized using composition TiO2 sol 75% and SiO2 25%. The result of the synthesis TiO2SiO2 composite was characterized by Fourier Transform Infra-Red (FT-IR) instrument to determine the functional groups in the composites and X-Ray Diffraction (XRD) instruments to determine the phase, crystallite size and degree of crystallinity in the composite. The purpose of this research is to synthesized TiO2SiO2 nanoparticle as a self cleaning agent with variation of the calcination temperature, to obtain composite characteristics that can support self cleaning. The self-cleaning ability was based on a produced composite characteristic of TiO2SiO2. The result of FTIR characterization showed that at calcination temperature of 400 °C, 450 °C, 500 °C, and 550 °C there was a Ti-OSi bond at the peak of 948.91 cm-1, 950.77 cm-1, 941.13 cm-1, 942.13 cm-1. The result of XRD characterization showed that at the temperature of 400 °C had the best characteristics, the 75.27% anatase phase and brookite phase 24.72%. Calcinations temperature 400 °C had best degree of crystallinity of 91.66%.